Cost of Tuberculosis Relapse in Yemen: A Nested Case-Control Study - Anaam, Mohamed Saif; Ibrahim, Mohamed Izham Mohamed; Serouri, Abdul Wahed Al; Bassili, Amal; Aldobhani, Adel (Journal of Pharmacy Practice and Community Medicine)
Background: The economic burden of tuberculosis (TB) in Yemen is enormous. Little empirical information is available about TB relapse-related cost incurred by government for treating relapse patients. Objective: The present study aims to estimate the direct cost of TB relapse from the government’s perspective. Materials and Methods: In the current study, a pharmacoeconomic analysis was conducted using the cost-of-illness method, which determines the direct and indirect costs of a specific disease. Forty-four relapse cases and 176 controls were included in the analysis. Results: T-test and Mann–Whitney U test showed a significant difference in mean and median of direct medical cost components. T-test also shows a significant difference in mean of the total relapse cost between males and females (P<0.05). The cost incurred by the government to treat one relapse case (US$92.31) was about three times more for that of treating a non-relapse (US$35.02), with an extra cost for a relapse case of US$57.29. It is estimated that cumulative costs for treating relapse cases (n=5764) reported through 1996-2010 was US$532,074.84. Conclusion: Study findings concluded that the cost to the government for the management of tuberculosis patients is substantial and inflicts considerable economic burden on the overall health care system of Yemen. The cost could be reduced by incorporating cost-effective strategies in tuberculosis control to prevent relapse.
Keywords: Cost; Nested; DOTs; Relapse; Tuberculosis; Yemen